Agent-based Modeling and Simulation for Evacuation of Landslides Natural Disaster - Zayn, Afta Ramadhan; Ramdani, Fatwa; Bachtiar, Fitra Abdurrachman (Faculty of Computer Science (FILKOM) Brawijaya University, 2020)
Landslides are natural disasters that pose a threat which is quite high in the area of Batu, East Java, Indonesia. The occurrence of landslides has a negative impact on environmental damage and even fatalities. These impacts can arise due to a lack of planning in disaster management preparedness. Therefore better planning is needed to minimize the negative impacts that arise. Improvement of planning can be done by conducting evacuation simulations. However, the existing evacuation simulation is still static with one scenario that is done repeatedly. Therefore, a more dynamic evacuation simulation is needed to represent the various parties involved in it and to apply various scenarios. Such dynamic simulations can be facilitated using agent technology. Agents can describe autonomous behaviour and can communicate in their environment to achieve a goal. Apply the capabilities of these agents by modelling and simulating the evacuation process can provide an illustration for a more dynamic process of landslide evacuation. This research presents an agent-based landslide evacuation model and the simulation results from this model. The results are concerned that, by using agent technology can apply simulations with various conditions. So with these results can be used as a reference in the handling of natural disasters that occur landslides.